Use of Recombinant Cell Permeable Small Peptides to Modulate Glucocorticoid Sensitivity of Acute Lymphoblastic Leukemia Cells - Geng, Chuan-dong (2010)
Glucocorticoid (GC) hormones induce apoptosis in T-cell and pre-B-cell acute lymphoblastic leukemia (ALL) cells. Steroid-mediated apoptosis requires a threshold level of the glucocorticoid receptor (GR) protein, and increasing the intracellular GR levels in ALL cells would augment their hormone-sensitivity. A protein transduction domain (PTD) approach was used to accomplish this. We produced an HIV Tat PTD domain fusion protein (Tat-GR(554-777)) that potentially competes for the degradation of GR protein by the ubiquitin-proteasome system and should thus increase its intracellular levels by “stabilizing” the GR. We also designed a fusion peptide for the c-Myb DNA binding domain, Tat-c-Myb DBD, since the biological function of this peptide as a dominant negative inhibitor of the c-Myb protein was already known. Purified, bacterially expresssed Tat-c-Myb DBD and Tat-GR(554-777) exhibited highly efficient transduction into cultured ALL cell lines including 697 (pre-B-ALL) and CEM-C7 (T-ALL) cells. As expected, the transduced Tat-c-Myb DBD peptide inhibited steroid-mediated stimulation of a GR promoter-luciferase reporter gene. Significantly, transduced Tat-GR(554-777) effectively increased intracellular GR levels in the GC resistant T-ALL cell line, CEM-C1, and in the pre-B-ALL 697 cell line. Furthermore, transduction of Tat-GR(554-777) rendered GC-resistant CEM-C1 cells sensitive to steroid killing and further sensitized 697 cells to steroid. The use of Tat-fusion peptide transduction may eventually lead to innovative therapeutic modalities to improve the clinical response of patients suffering from T-cell and pre-B-cell acute lymphoblastic leukemia by increasing steroid-responsiveness and perhaps converting steroid-resistant leukemia to a hormone-responsive phenotype.